Pesquisa de Rickettsia sp e agentes causadores de erliquiose (Anaplasmataceae) em carrapatos colhidos em cães e domicílios nas áreas urbana e industrial no Município de Cubatão - Estado de São Paulo, 2011-2012 - Botelho, Mônica Luzia de Arruda (2013)
Between August 2011 and May 2012, 100 samples of ticks were collected from infected environments and domestic or stray dogs in the city of Cubatão, with a total amount of 828 specimens, 827 Rhipicephalus sanguineus and 01 Amblyomma ovale. The parasites were subdivided into three groups: a) collected from dogs taken to the city pound; b) collected from dogs in the city¿s veterinary clinic c) collected from dogs during a zoosanitary visit. In this group, parasites collected in infested homes were included. A convenience sample of 26 ticks was separated according to the address of collection and the investigation of Rickettsia sp, spotted fever Rickettsias and the Ehrlichia sp group in these ticks was conducted by means of Polymerase Chain Reaction (PCR). All samples showed negative for Rickettsia sp. For Ehrlichia sp all samples were negative for the dsb gene and six samples showed positive for the 16S gene (RNA ribosomal). The results demonstrate positivity in these specimens for a bacteria from the Anaplasmataceae family, which was also present in the only specimen of Amblyomma ovale collected. In conclusion, although no positivity was found for Rickettsia sp, the zoonotic risk for erlichiosis should be considered. Besides this, an increase in the sampling submitted to PCR could furnish more information concerning the risk of infection by Rickettsia sp in ticks in the city studied.